Acquisition of English Argument Patterns By Russian EFL Students - Amatov, Alexander Mikhailovich (2021)
Foreign (especially English) language learning has witnessed growing popularity in Russia over the last decades due to the enormous change in economic, political, legal, and cultural domains in the current period. The increasing need for good English speaking and writing skills put forward a demand for the accurate use of lexical items and grammatical structures by those who study English as a foreign language (EFL). Lexical and grammatical accuracy acquires a crucial importance in reasoning and argumentation. A slapdash word or syntactic construction in the argument structure may submit the listener to a conclusion, which is completely different from what the speaker implied. Such issues may be particularly frustrating in academic, legal, business, medical, and other types of institutional discourse. The rules of Aristotelian logic, underlying the good majority of reasoning structures, are generic. Therefore, it is a certain difference between the two languages, native (Russian) and foreign (English), that makes Russian students of English misinterprete logical chains and use irrelevant lexical items and grammatical constructions.